Economic Scratch on the Future Growth Path of Bangladesh: An ARIMA Approach - Ferdous, Refat (International Journal of Publication and Social Studies, 2022)
The purpose of this study is to investigate the future growth path (growth rate) of Bangladesh. Bangladesh is one of the fastest-growing nations in the world. To secure sustainable and spontaneous economic development, contentious increasing economic growth is a prerequisite. In this paper, Autoregressive Integrated Moving Average (ARIMA) model is used to track down the future growth path of Bangladesh. Time series data from year 1972 to 2018 has been utilize to predict the economic growth for year 2019 to 2028. By using the ARIMA approach it has been found that next 10 years (2019-2028) the GDP growth of Bangladesh will be reduced from the current growth rate. The average GDP growth rate from the year 2019-2026 will be clustered near 5% and in the year 2027 it will be peak by 8.77% and the following year growth rate will be consolidated by 1.39%.